Analysis of Factors Affecting the Performance of Government Project Completion Time in Pangkalpinang City - Giarta, Fanta Wahyu; Suroso, Agus (Universitas Ibn Khaldun Bogor, 2025)
Bangka Belitung Islands Province with its capital city Pangkalpinang has a strategic position as a city located on the economic route of Bangka Island. As an archipelago, it relies heavily on the transportation sector, both land, sea and air transportation to meet construction materials. Astronomically, Pangkalpinang City is located between 2°4’-2°10’ South Latitude and 106°4’-106°7’ East Longitude. Administratively, Pangkalpinang City is divided into 7 sub-districts, namely Bukit Intan, Girimaya, Taman Sari, Gerunggang, Rangkui, Gabek, and Pangkalbalam Districts with a total area of ​​118.41 km2. This research is included in the type of quantitative descriptive research using the survey method. The survey method aims to provide a detailed description of the background, characteristics, and characteristics that are typical of a case or incident of something that is general in nature. The purpose of the study was to obtain solutions to the variables that most influence the performance of the completion time of government building construction in Pangkalpinang City. Based on the results of the T-Test analysis, F-Test and Determination Coefficient Test, it was obtained partially and simultaneously that Environmental Factors (X1), Wage Factors (X2), Coordination (X3), and Worker Productivity (X4) have a significant effect and have a contribution of 85.4% to the performance of the completion time of government building construction projects, 2) based on the results of the variable ranking analysis using multiple linear regression equations & beta coefficient values, it can be concluded that the Wage Factor variable (X2) is the dominant factor that influences the performance of the completion time of building construction projects, which is 72.59%, so to control the completion time of government building construction projects which is mainly carried out by the Project Manager is to control Wages, 3) all research variables, namely Environmental Factors (X1), Labor Factors (X2), Coordination (X3), and Worker Productivity Factors (X4) can affect the performance of the completion time of government building construction projects in Pangkalpinang City. The results of the analysis show that the dominant factor according to all respondents is the labor factor (beta value 1.001).